Examination of the health status of populations from depleted-uranium-contaminated regions - MILACIC, Snezana; PETROVIC, Dragana; JOVICIC, Dubravka; KOVACEVIC, Radomir; SIMIC, Jadranko (Environmental research, 2004)
During the NATO air strikes on the Federal Republic of Yugoslavia (Serbia and Montenegro) in 1999, depleted-uranium ammunition was used on 112 locations, mainly Kosovo, in the south of Serbia, and one location in Montenegro. Blood samples of residents from depleted-uranium-contaminated areas were gathered and blood cell and chromosomal aberrations were analyzed. During the last 3 years blood samples from 21 residents of Kosovo (Štrpce), from 29 residents from the south of Serbia (the Vranje and Bujanovac regions), and from 19 technical television workers from the site of Pljačkovica, in the vicinity of Vranje, were collected. Blood samples from 33 residents of central Serbia and 46 occupational workers exposed to X-rays were used as controls. All subjects studied were without any clinical symptoms of disease. The examinations included general clinical assessment; urine samples for α-and γ-spectrometry analysis; complete blood counts; ratio-percentages of blood cells in stained (Giemsa) capillary smears, individual leukocyte line elements; morphological changes observed under a microscope; the presence of immature forms or blasts; and leukocyte enzyme activity [alkaline phosphatase leukocyte (APL)]. Chromosomal aberrations were evaluated in 200 peripheral blood lymphocytes in mitosis. An increased incidence of rogue cells and chromosomal aberrations was found in the blood of the residents of Vranje and Bujanovac, but this was below the incidence of chromosomal aberrations in individuals occupationally exposed to ionizing irradiation. Blast cells were not found. Blood counts were decreased in only a few samples, while morphological changes of both nuclei and cytoplasm were marked in individuals in south and central Serbia. Enzymatic activity (as measured by the APL score) was decreased in samples with chromosomal aberrations and cyto-morphological changes in subjects from the south of Serbia. The contamination level measured by this examination was low. Because of the presence of depleted uranium (uranium-238) in the soil and in plants, the prevention of consequences necessitates the identification of the initial biological effects on sensitive tissues. Early identification of serious blood cell changes is important for appropriate medical treatment.